Piezo1 regulates autophagy in HT22 hippocampal neurons through the Ca2+/Calpain and Calcineurin/TFEB signaling pathways - Yatong Wu; Yan Lu; Hao Zhang; Suhe Dong; Ziqing Zhang; Sinian Wang; Fengsheng Li; Shimin Yin (PLoS ONE, 2025)
Objective To investigate the functional and molecular mechanisms by which Piezo1regulates HT-22 hippocampal neuronal autophagy, and to explore whether Piezo1 regulates hippocampal neuronal autophagy via the Ca2+/Calpain, CaMKKβ, or Calcineurin pathways. Methods The impacts of Piezo1 inhibition, activation and gene knockdown on the autophagy of HT22 neurons was investigated by Western blotting, PCR and immunofluorescence. The changes of intracellular calcium (Ca2+) concentration were also observed. To pinpoint the specific downstream Ca2+ signaling pathway by which Piezo1 modulates autophagy, the calcium chelator BAPTA-AM, the Calpain inhibitor PD151746, and the CaMKKβ inhibitor STO609 were employed either alone or in combination. Results Enhanced autophagy was observed when Piezo1 was activated using the agonist Yoda1, manifesting as increased release of autophagic vacuoles, enhanced LC3 II/LC3 I ratio, decreased p62 protein level, and elevated nuclear translocation and expression of the TFEB protein. ATG7 knockdown by ATG7 shRNA mitigated the effects of Yoda1 on LC3 II/LC3 I ratio and p62 protein levels. The Piezo1 inhibitor GsMTx4 partially reversed the autophagy caused by starvation in HT22 neurons while Yoda1 still activated autophagy in the presence of BDNF. Following Piezo1 knockdown, neuronal autophagy was decreased. Piezo1-induced autophagy was accompanied with an increased cytoplasmic concentration of Ca2+. The calcium chelator BAPTA-AM partly reversed Piezo1 activation-induced autophagy, which was also mitigated by blocking calcineurin/TFEB signaling or Calpain signaling. Conclusion Piezo1 modulates the autophagy of HT-22 neurons by activating Ca2+/Calpain and Calcineurin/TFEB pathways.